2018
DOI: 10.1155/2018/1232583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Newer Antidiabetic Drugs on Endothelial Function and Arterial Stiffness: A Systematic Review and Meta-Analysis

Abstract: Background Newer antidiabetic drugs, i.e., dipeptidyl peptidase-4 (DPP-4) inhibitors, sodium-glucose cotransporter-2 (SGLT-2) inhibitors, and glucagon-like peptide-1 receptor agonists (GLP-1 RAs) may exert distinct cardiovascular effects. We sought to explore their impact on vascular function. Methods Published literature was systematically searched up to January 2018 for clinical studies assessing the effects of DPP-4 inhibitors, GLP-1 RAs, and SGLT-2 inhibitors on endothelial function and arterial stiffness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 56 publications
(53 reference statements)
2
73
2
Order By: Relevance
“…Furthermore, antihypertensive, hypolipidemic, and antidiabetic drugs may affect arterial stiffness. [48][49][50][51][52] In our study, no significant differences in the drug therapy were observed among AAA patients with and without CAD.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, antihypertensive, hypolipidemic, and antidiabetic drugs may affect arterial stiffness. [48][49][50][51][52] In our study, no significant differences in the drug therapy were observed among AAA patients with and without CAD.…”
Section: Discussioncontrasting
confidence: 58%
“…24,25 A recent meta-analysis conducted to investigate the effects of newer antidiabetic drugs demonstrated that the SGLT2 inhibitor dapagliflozin might influence arterial stiffness. 26 Beyond these results, the rapidity with which the effect is obtained in our study is interesting and worthy of comment. Indeed, endothelial function improves after 1 month of treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Concerning the effect of incretin‐based agents on arterial stiffness, we have just to mention a recently published systematic review and meta‐analysis by Batzias and colleagues summarizing all relevant evidence . The authors demonstrated that both dipeptidyl peptidase‐4 (DPP‐4) inhibitors and glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are associated with a significant reduction in PWV, although the small sample size of included studies and the substantial observed heterogeneity led the authors to conclude that the results of their meta‐analysis should be interpreted with caution …”
Section: The Effect Of Other Antidiabetics On Arterial Stiffnessmentioning
confidence: 99%